2020
DOI: 10.1002/wer.1421
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of acid‐treated, base‐treated, and Fenton‐like reagent‐treated biomass for Cr(VI) sequestration from aqueous solutions

Abstract: A wide variety of biomass materials have been used for the removal of toxic chromium(VI) by biosorption. The current study investigated the efficacy of Macadamia nutshells treated with sodium hydroxide, nitric acid, and the Fenton‐like reagent in the removal of Cr(VI). The adsorbents were characterized by FTIR, SEM, TGA, and elemental analysis. Effects of functional parameters influencing the adsorption of Cr(VI), solution pH (pH 1–11), contact time (5–250 min), concentration of adsorbent (1–10 g/L), and adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…The intra-particle diffusion, Elovich, pseudo-second order (PSO), and pseudo-first order (PFO) models were used to gain insights on the chemical reaction processes influencing the uptake of Cr(VI) in relation to time, mass transfer, and the rate-limiting step. [46] The non-linear equations of the PFO, PSO, and Elovich rate models are illustrated in Eqs. ( 6), (7), and ( 8).…”
Section: Data Treatmentmentioning
confidence: 99%
“…The intra-particle diffusion, Elovich, pseudo-second order (PSO), and pseudo-first order (PFO) models were used to gain insights on the chemical reaction processes influencing the uptake of Cr(VI) in relation to time, mass transfer, and the rate-limiting step. [46] The non-linear equations of the PFO, PSO, and Elovich rate models are illustrated in Eqs. ( 6), (7), and ( 8).…”
Section: Data Treatmentmentioning
confidence: 99%
“…Several studies have demonstrated improved Cr (VI) adsorption performance due to pretreatment of the adsorbent surface. For instance, a study by Obakeng et al (2020) examined the Cr (VI) removal efficiency of macadamia nutshells treated with sodium hydroxide, nitric acid, and fenton-like reagents. The study findings revealed that the base-treated adsorbent demonstrated maximum Cr (VI) adsorption performance at 98% compared to the acid and fenton-treated adsorbent.…”
Section: Cr (Vi) Removal Studies By Low-cost Biomass and Agro-based A...mentioning
confidence: 99%
“…The high IEP (pH 11.69) observed for AC-Fe3O4-SiO2-PEI was attributed to the cationic characteristic of PEI [38,39]. The pH of a solution affects the surface chemistry of adsorbents, ionization, and bioavailability of adsorbates [25,40]. Hence, the investigation of its influence on adsorption is crucial.…”
Section: Influence Of Solution Ph On Adsorption Of Cr(vi)mentioning
confidence: 99%